AN ANALYSIS OF TEACHER’S SOCIAL COMPETENCE IN TEACHING ENGLISH OF SMP NEGERI 2 HILIDUHO 2023/2024 - Batee, Ribka Trimulia; Harefa, Afore Tahir; Maru'ao, Nursayani; Zega, Riswan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Teacher social competence is the teacher's ability to do something, Engage in productive and efficient communication and interaction with students, colleagues, parents, and the community at large.and does not differentiate between ethnicity, race and language. Teachers who are able to build good interaction or communication relationships in the school environment will be one of the elements of a teacher's success in applying their attitudes and social skills. The purpose of this research is to obtain information about teachers' social competence and its application in the educational environment, especially for students learning English. The research method used is qualitative analysis. The instruments in this research are observation and interviews. Data was obtained from observations and interviews with English teachers. Based on the results of observations and interviews, the factors that influence teachers' social competence are beliefs and values, skills, experience, personality, motivation, emotional, intellectual abilities and organizational culture. Meanwhile, the way teachers apply social competence is that English teachers carry out communication relationships that are inclusive, objective, non-discriminatory, effective and empathetic. Furthermore, teachers adapt to the school environment and surrounding community, by building collaborative relationships with fellow educators in developing English language learning. English teachers also collaborate with parents of students in overcoming student learning problems. However, based on teachers' social competence in Minister of Education Regulation Number 16 of 2007, English teachers do not collaborate with parents in creating learning programs